Slope Reinforcement Using Gabion Retaining Wall On Angke River In Perumahan Curug Residence Griya Elok West Bogor District - Lutfi, Muhamad; Chayati, Nurul; Rulhendri, Rulhendri; Insan, Muhammad Khaerul; Handrianto, Yayan (Universitas Ibn Khaldun Bogor, 2024)
Bogor City is located between 106,480 E and 6,360 S and has an average altitude of at least 190 m, a maximum of 350 m, slope between 0.3%, 4-15%, 16-30% and above 40% with a distance of approximately 60 km from the capital, surrounded by Mount Salak, Mount Pangrango and Mount Gede. Bogor City has annual rainfall between 3500-4000 mm with an area of 4,992.30 Ha, between 4000-4500 mm with an area of 6,424.65 Ha, and between 4500-5000 mm with an area of 433.05 Ha mainly in December to January. (kotabogor.go.id). On 27 April 2019, landslides occurred due to heavy rain in Perumahan Curug Residence Griya Elok Jalan Parvi Bojong Neros RT. 03/ 07, Curug Village, West Bogor District, Bogor City. It is necessary to plan the retaining wall to mitigate the impacts of the landslide disaster. The access road in Curug Residence is an asphalt road with a width of 2.5 m, this causes only small vehicles to be able to pass in the area. In consideration of the narrow access road, heavy equipment cannot enter the Curug Residence landslide location, in order to deal with landslides, a gabion-type retaining wall will be applied. The gabion retaining wall is more efficient and practical with narrow road access because it can be done directly on site and does not require any heavy equipments. The results of the analysis of gabion retaining walls can be concluded as follows, the dimensions of the gabion retaining wall construction are 9.5 meters high, the width of the foot slab is 1.58 meters, and the thickness of the wall top section slab is 0.79 meters. After the calculation, the result of stability factor to shear is 3,624 > 1,5 and stability to bolsters is 5,858 > 1,5. Then it can be concluded that the gabion retaining wall is safe against danger of shear, bolsters and soil bearing capacity. The construction cost is Rp2.735.000.000,- and requires 127 days or 3 months and 1 week of construction work.